Formation of sustained antitumor effect in mice’s liver and spleen (CBA х C57BL/6)F1 after a single intravenous injection of zymosan-treated neutrophils - A. G. Lyubimov; G. Y. Lyubimov; V. A. Kozlov (Acta Biomedica Scientifica, 2016)
Application of zymosan in medicine is limited because of its side effects, since the native granules of zymosan directly activate serum complement components and phagocytic cells. In this regard, it was decided at the outset (ex vivo) to incorporate the granules of zymosan in the neutrophils, and only then inject these "loaded" zymosan neutrophils into the bloodstream. Our experiments showed a total inhibition of the weight accretion of both tumor affected liver (from 5220 ± 963 to 1327 ± 219 mg) and spleen (from 328 ± 29 to 187 ± 64 mg) of mice. Thus these data showed that even on the 17th day after a single intravenous injection zymosan-treated neutrophils persist expressed manifestations of anti-tumor activity in the liver and spleen, that may be basis for using this method for antimetastatic preventive measures in liver and other localizations.